The Characteristics of Macrophage Heterogeneity in Atherosclerotic Aortas - Song, Yu-Jie; Ma, Yu; Meng, Ting; Zhuang, Tao; Ruan, Cheng-Chao; Li, Yan; Zhang, Guan-Nan (Journal of cardiovascular translational research, 2024)
Macrophage is the main effector cell during atherosclerosis. We applied single-cell RNA sequencing (scRNA) data to investigate the role of macrophage subsets in atherosclerosis. Monocyte and macrophage clusters were divided into 6 subclusters. Each subcluster’s markers were calculated and validated by immunofluorescence. Elevated macrophage subclusters in the WD group were subject to enrichment pathway analysis and exhibited different phenotypes. Pseudotime analysis shows the subclusters originate from monocytes. We cultured bone marrow-derived macrophages with CSF-1 and ox-LDL to simulate an atherosclerotic-like environment and detected the transformation of subclusters. Macrophage-Vegfa and Macrophage-C1qb increased in the WD group. Macrophage-Vegfa acquires the characteristics of phagocytosis and immune response, while Macrophage-C1qb is not involved in lipid metabolism. The two subclusters are both enriched in cell movement and migration pathways. Experimental verification proved Monocyte-Ly6C evolved into Macrophage-Vegfa and Macrophage-C1qb during atherosclerosis progression. Graphical Abstract